Desarrollo de indicadores de sostenibilidad ambiental de la microcuenca del Campus Salache de la Universidad Técnica de Cotopaxi, periodo 2022. - Moreta Muela, Cinthia Lizbeth (2022)
The present research work focused on the development of environmental sustainability indicators of the micro basin of the Experimental Center, Salache Campus of the Technical University of Cotopaxi, mainly water management and land use. Within the project, a sustainability plan was proposed where indicators are established that could improve the environmental management system within the university in its application. The methodology used consisted of the qualitative study of the characteristics determined by academic activities about water, soil, and biodiversity resources, through the collection of data from the sector for the characterization of environmental conditions, through bibliographic research in conjunction with descriptive research, and by observation, allowing study of the environmental system that develops in the institution, for the construction of the tables, tools such as sustainable measurement systems were available in third-level educational centers, which served as a guide for the elaboration of the indicators, so formulas were located that could be applied to the factors studied in each indicator. The results that were obtained within the current environmental characterization of CEASA contemplate the biophysical components, hydrological background, geomorphological background, the edaphological background of water, soil and the distribution in terms of fauna and flora, and the environmental conditions of water and soil were identified, finding the lack of wastewater treatment, which has led to pollution modifying the composition and altering the pH, Electrical Conductivity, Dissolved Oxygen among others, in the case of the soil, the change of climate and anthropic practices have modified some characteristics such as texture. Once the environmental conditions of the resources were established, the indicators that could add sustainable practices that improve the environmental situation of the experimental center were chosen, such as the adhesion of more sustainable mechanisms in the internal systems of the campus. Based on the results, we concluded that the campus is in a situation susceptible to improvement within the area of environmental sustainability due to the high index of wastewater contamination due to the lack of gray water treatment and the texture change that has been taking place on the campus, prioritizing the educational and environmental system to guarantee the well-being of the university community contributing to sustainable development.